Mindfulness-based therapies in the treatment of somatization disorders: a systematic review and meta-analysis. - Shaheen E Lakhan; Kerry L Schofield (PLoS ONE)
Background Mindfulness-based therapy (MBT) has been used effectively to treat a variety of physical and psychological disorders, including depression, anxiety, and chronic pain. Recently, several lines of research have explored the potential for mindfulness-therapy in treating somatization disorders, including fibromyalgia, chronic fatigue syndrome, and irritable bowel syndrome. Methods Thirteen studies were identified as fulfilling the present criteria of employing randomized controlled trials to determine the efficacy of any form of MBT in treating somatization disorders. A meta-analysis of the effects of mindfulness-based therapy on pain, symptom severity, quality of life, depression, and anxiety was performed to determine the potential of this form of treatment. Findings While limited in power, the meta-analysis indicated a small to moderate positive effect of MBT (compared to wait-list or support group controls) in reducing pain (SMD = -0.21, 95% CI: -0.37, -0.03; p<0.05), symptom severity (SMD = -0.40, 95% CI: -0.54, -0.26; p<0.001), depression (SMD = -0.23, 95% CI: -0.40, -0.07, p<0.01), and anxiety (SMD = -0.20, 95% CI: -0.42, 0.02, p = 0.07) associated with somatization disorders, and improving quality of life (SMD = 0.39, 95% CI: 0.19, 0.59; p<0.001) in patients with this disorder. Subgroup analyses indicated that the efficacy of MBT was most consistent for irritable bowel syndrome (p<0.001 for pain, symptom severity, and quality of life), and that mindfulness-based stress reduction (MBSR) and mindfulness-based cognitive therapy (MCBT) were more effective than eclectic/unspecified MBT. Conclusions Preliminary evidence suggests that MBT may be effective in treating at least some aspects of somatization disorders. Further research is warranted.